KELAYAKAN SMART CARD PADA SUBMATERI PEMANFAATAN KEANEKARAGAMAN HAYATI INDONESIA KELAS X - Dian, Vivi Mirtha; Syamswisna, Syamswisna; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aims to measure the feasibility of smart card media on the sub-material Indonesian Biodiversity Utilization Class X on the benefits of medicinal plants by community in Seberkat village.. This study was conducted in a form of qualitative research using the descriptive method. The sample was taken using a purposive sampling technique. Based on the analysis of the syllabus, the results of the research were implemented into smart card media. The smart card was tested by five validatoryÂ using the Likert scale and was analyzed using the Lawshe method (1975). Two lecturers of the Biology Education Study Program of FKIP UNTAN and three Biology teachers from SMAN 1 Tebas, SMAN 2 Tebas, and SMA Muhammadiyah 2 Pontianak participated in testing the media feasibility. The smart card media obtained Content Validity Index (CVI) scores by 0,96 from five validatory with a valid category and is suitable to use on the sub-material Indonesian Biodiversity Utilization, yet still needs to be tested into the classroom. Keywords: Indonesian Biodiversity, medicinal plants, smart card.Â